PERAN PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA DALAM UPAYA PENCEGAHAN STUNTING DI KALURAHAN SELANG KAPANEWON WONOSARI KABUPATEN GUNUNGKIDUL - Suindartini, Suindartini; Lestari, Rosalia Widhiastuti Sri (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
This research aims to determine the role of Family Empowerment and Welfare (PKK) in efforts to prevent stunting in Selang Village, Kapanewon Wonosari. This research uses a descriptive qualitative method, which begins with observation, and uses interview methods and a literature approach to conduct related studies. At the same time, I want to know about the programs that have been implemented by the PKK of Selang Village, Kapanewon Wonosari, Gunungkidul Regency in efforts to prevent stunting. The analysis was carried out using Edward III theory, based on 4 (four) indicators, namely resources, communication, disposition and bureaucracy. The research results show that PKK cadres in Selang District have played an active role as agents of change in implementing stunting prevention through implementing the PKK priority program. Priority programs that have been implemented by the PKK are child rearing patterns implemented by Working Group (Pokja) I, skills training and development of Family Income Increase Business (UP2K) implemented by Pokja II, optimization of yard land with the 3K Movement (Cages, Ponds and Gardens), and socialization of Diverse, Nutritious, Balanced and Safe (B2SA) food is carried out by Pokja III, outreach activities on Clean and Healthy Lifestyles (PHBS) and assistance to pregnant women and brides-to-be are carried out by Pokja IV.Keyword: Family Empowerment and Welfare (PKK); Interval; Role; Stunting.